(untitled) (CIPEEX, 2025)
Objective: To identify the role of bariatric surgery in the treatment of obesity. Method: systematic review of the literature, guided by the question: “What is the role of bariatric surgery in the treatment of obesity?”. To answer this question, 20 original articles published between 2019 and 2024 were selected from the PubMed, SciELO, and LILACS databases. The descriptors used included “bariatric surgery,” “obesity,” “weight reduction,” “quality of life,” “comorbidities,” “postoperative complications,” and their corresponding English terms, combined with the Boolean operators “AND” and “OR.” Results: The bariatric techniques Laparoscopic Vertical Gastrectomy (LSG), Roux-en-Y Gastric Bypass (RYGB), and Single-Anastomosis Gastric Bypass (OAGB) resulted in significant weight loss and improvements in quality of life. OAGB was the most effective in long-term weight loss. RYGB provided sustained weight loss and resolution of comorbidities, but with a greater need for nutritional supplementation. LSG had a higher prevalence of esophagitis and GERD (Gastroesophageal Reflux Disease), while OAGB showed fewer serious complications and better metabolic outcomes. Conclusions: All techniques proved effective for the management of obesity and its comorbidities, each with advantages and challenges. The choice should be personalized, with continuous monitoring, especially to avoid nutritional deficiencies in RYGB and OAGB and to manage GERD in LSG.